The Importance of the Metacommunicative Purposes of Communication, or Teaching Students to Listen and Speak Like Normal Human Beings - Viaggio, Sergio (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThis article submits that utterances are always uttered in a specific social context and are produced and understood out of specific metacommunicative purposes. There is more to communication than the exchange of propositions. Real comprehension is always top-down and relevance-governed, and succeeds at the level of metarepresented cognitive and pragmatic meaning. If students are not taught to understand and speak meaningfully, they fall into the trap of modular comprehension, memorization and verbalization.